2005
DOI: 10.1200/jco.2005.04.126
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey on Complementary and Alternative Medicine in Cancer Patients in Japan

Abstract: This survey revealed a high prevalence of CAM use among cancer patients, without sufficient information or consultation with their physicians. Oncologists should not ignore the CAM products used by their patients because of a lack of proven efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
193
9
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(228 citation statements)
references
References 26 publications
(14 reference statements)
18
193
9
3
Order By: Relevance
“…The use of complementary and alternative medicine (CAM) is a growing field in health care, particularly among cancer patients in the advanced stages of disease. However, recent reports have shown that while expenditure on CAM is high, 44.6%-66.7% of cancer patients receiving palliative care use CAM without sufficient information [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of complementary and alternative medicine (CAM) is a growing field in health care, particularly among cancer patients in the advanced stages of disease. However, recent reports have shown that while expenditure on CAM is high, 44.6%-66.7% of cancer patients receiving palliative care use CAM without sufficient information [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that natural sources can provide novel and structurally diverse chemical compounds possessing anti-cancer properties and many have been approved recently by the EMA and FDA, for example, Kadcylaand Istodax. Although there is beneficial effects of using CAM as shown here based on clinical studies, there is lack of useful and effective communication between clinicians and patients about CAM therapies, since many CAM users engage in this kind of treatment without consulting their orthodox healthcare providers (Hyodo, Amano et al 2005;Evans, Shaw et al 2007). This is one of the factors which has led to the debate among healthcare practitioners about the place of CAM within the framework of mainstream medicine (Kissane, Bultz et al 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In the UK, relaxation and meditation techniques, spiritual or faith healing, reflexology, aromatherapy, and mineral and herbal products are the most common modalities used by cancer patients (Scott, Kearney et al 2005). In Malaysia, Japan, Palestine and Australia, nutritional supplements, herbal products and multivitamins are the most common CAM therapies (Hyodo, Amano et al 2005;Farooqui, Hassali et al 2015;Sullivan, Gilbar et al 2015;AliShtayeh, Jamous et al 2016). Multivitamins are also regularly used in the US, as well as chiropractic or osteopathic manipulation, movement therapies, special diets; such as organic vegetables and fruit, gluten free, casein free, no processed sugars or no salicylates; acupuncture, naturopathy, or different combinations of these therapies (Shih, Chiang et al 2009;Perrin, Coury et al 2012;Falci, Shi et al 2016).…”
Section: Cam and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A Japanese study reported 44.6% CAM use among cancer patients (9). According to Montazeri et al study, 219 out of 625 Iranian cancer patients used CAM and indicated that apart from prayer and spiritual healing, the use of other common methods of CAM among Iranian cancer patients is unpopular (10).…”
Section: Introductionmentioning
confidence: 99%